EXAMINING OF SHORT CHAIN FATTY ACIDS – METABOLITES OF PERIODONTAL PATHOGENIC FLORA – AS MARKERS OF DIAGNOSTIC OF MICROBIOCENOSIS OF ORAL CAVITY - O.L. Lychkovska; G.M. Melnychuk (Український стоматологічний альманах, 2018)
Introduction. It has been established thus far that periodontal pathogenic flora is the leading factor in the development of generalized periodontitis (GP) as it produces endotoxins, proteolytic enzymes, as well as short chain fatty acids (SCFA), which have significant damaging potential for periodontal tissues.